(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Shalyatantra, a significant section of Ayurveda, encompasses descriptions of surgical and para-surgical methods. Venereal diseases are illnesses often transmitted through sexual contact with an infected person, presenting a major global health concern, especially for pregnant women and newborns. Surgical and Para surgical interventions for venereal diseases in men are not widely known or discussed in Ayurveda. The scope and indications for these interventions are not well-explored. Common venereal diseases include chlamydial infection, gonorrhea, hepatitis, human papillomavirus, and genital herpes. If left untreated, chlamydia, a significant sexually transmitted bacterial infection, can lead to urethritis, which can be addressed through a surgical intervention known as perineal urethrostomy. Complications of gonorrhea, caused by the sexually transmitted bacterium Neisseria gonorrhoea, include phimosis, balanitis, and paraphimosis. These complications can be managed with surgical operations like the plastibell technique and circumcision. For Charmakeelam, parasurgical procedures such as Agni karma and Kshara karma are utilized for treatment. Genital herpes blisters can be surgically removed. In the case of Upadamsam, treatments like Siravyadham in Medramadhyam and Jalookavacharanam are listed as effective remedies for venereal disorders. Surgical procedures like Chedhanam, Bedhanam, and Visravanam, along with para-surgical techniques such as Kshara Karma, Agni Karma, and Jalookavacharanam, are described for various venereal diseases. In summary, both modern science and Ayurveda offer numerous surgical and para surgical methods to manage a wide range of ailments, including venereal diseases.